Wage assimilation of immigrants and internal migrants: the role of linguistic distance. Issue 10 (3rd October 2018) - Strøm, Steinar; Piazzalunga, Daniela; Venturini, Alessandra; Villosio, Claudia
ABSTRACT: This paper investigates the wage assimilation of foreign immigrants and internal migrants in Italy, comparing them with stayers. Control for the selection in out-migration is performed using a new duration version of the Heckman correction and by taking into account both return migration and moves to other destinations. Internal migrants experience only minor wage differences when compared with stayers. By contrast, foreign immigrants earn about 8% less than stayers and internal migrants at the beginning of their careers, and the wage gap increases over time. Both language distance and job segmentation contribute to immigrants' lack of wage assimilation.